Phytochimiques des plantes médicinales utilisées dans la prise en charge des maladies infantiles au SudBénin - Sabine Aribikè Kouchadé; Arlette Raymonde Adjatin; Aristide Cossi. Adomou; Hospice Gbèwonmèdéa Dassou; Akpovi Akoègninou (European Scientific Journal, ESJ, 2017)
In southern Benin, medicinal plants are used for the health care of children aged 0 to 12 years. The present study aims to highlight some medicinal plants used in southern Benin to treat childhood diseases including malaria, candidiasis, teething disorders, infant colic and diarrhea. The phytochemical screening of the leafy stems of the selected plants revealed the presence of alkaloids, tannins (gallic and catechic), coumarins, anthocyanins and leuco-anthocyans, quinone derivatives, triterpenoids, steroids, saponosides and reducing sugars. These various metabolites possess various therapeutic properties involved in the treatment of the indicated disorders. This would confirm the therapeutic uses reported by the populations surveyed. However, the evaluation of antimalarial, antibacterial, anti-inflammatory and analgesic activities as well as the toxicity test of the aqueous extract of these plants would be necessary.